2022
DOI: 10.3390/pathogens11121547
|View full text |Cite
|
Sign up to set email alerts
|

The Double Game Played by Th17 Cells in Infection: Host Defense and Immunopathology

Abstract: T-helper 17 (Th17) cells represent a subpopulation of CD4+ T lymphocytes that play an essential role in defense against pathogens. Th17 cells are distinguished from Th1 and Th2 cells by their ability to produce members of the interleukin-17 (IL-17) family, namely IL-17A and IL-17F. IL-17 in turn induces several target cells to synthesize and release cytokines, chemokines, and metalloproteinases, thereby amplifying the inflammatory cascade. Th17 cells reside predominantly in the lamina propria of the mucosa. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 177 publications
0
14
0
1
Order By: Relevance
“…In addition to their defensive action against pathogens, members of the IL-17 family can exacerbate tissue injury, because of their pro-inflammatory activity. IL-17 induces neutrophil recruitment, activation of the innate immune system, and enhancement of B-lymphocyte functions [ 48 ]. It has been reported that IL-17 levels correlate with SLEDAI in patients with LN [ 49 , 50 ].…”
Section: Sle Pathogenesismentioning
confidence: 99%
“…In addition to their defensive action against pathogens, members of the IL-17 family can exacerbate tissue injury, because of their pro-inflammatory activity. IL-17 induces neutrophil recruitment, activation of the innate immune system, and enhancement of B-lymphocyte functions [ 48 ]. It has been reported that IL-17 levels correlate with SLEDAI in patients with LN [ 49 , 50 ].…”
Section: Sle Pathogenesismentioning
confidence: 99%
“…It has also been observed that nasal colonization with S. aureus is often present in GPA, especially in relapsing patients. It has been suggested that this pathogen might contribute to an inflammatory microenvironment necessary for the activation of autoreactive T cells in AAV [ 70 , 71 ]. The direct pathogenicity of ANCA is supported by both experimental and clinical observations [ 72 , 73 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…In addition, introducing the IRAK4 kinase dead in knock-in mice was shown to cause resistance to the induction and progression of Th17-cells driven experimental autoimmune encephalomyelitis [ 76 ]. It is worth mentioning that Th17-cells are considered as key pathogenic T cells involved in multiple inflammatory and autoimmune diseases [ 77 ]. Also, lupus-prone mice harboring the kinase-inactive IRAK4 showed reduced glomerulonephritis, splenomegaly, serum anti-nuclear antibodies and lower TNF-α expression in macrophages compared with lupus-prone mice with functional IRAK4 [ 74 ].…”
Section: Irak4mentioning
confidence: 99%